BETWEEN THE SA’ALIK AND THE EARLY MUSLIMS: A JAMESONIAN READING ON LAMIYYAT AL-ARAB - Wawan Eko Yulianto (PARADIGM: Journal of Language and Literary Studies, 2020)
This article aims to propose a possible answer to the curious case of the popularity of Lamiyyat al-Arab as a means of education among Muslim leaders during the Umayyad era. The curiosity lies in the fact that Lamiyyat al-Arab is attributed to al-Shanfara, who was reportedly a su’luk, an outcast in the society who was also known as a brigand poet. To answer the curiosity, I conducted a literature review on who the sa’alik are and how they share some vision with early Muslims. This exploration makes up the first part of the essay. The second half of the essay is a textual interpretation on Lamiyyat al-Arab guided by the three horizons of interpretation as proposed by Fredric Jameson. Looking at three different horizons of meaning, textual, social, and historical, I strongly hope that the interpretation offer a glimpse into the desire for change that the poem shares with the early Muslims. This constitutes as a possible answer to the curious popularity of the pre-Islamic poem among early Muslims.